Intangible resources in strategic management of organizations - Pietruszka-Ortyl, Anna (Management and Administration Journal, 2019)
The paper concentrates on showing the role of intangible assets in gaining the competitive advantage of modern organizations and their importance in strategic management organizations. The starting point of deliberations is insightful presentation of the resource-based theory basic assumptions and the discussion of the attributes of the resources that are the most valuable for contemporary organizations. In turn literature overview of different classifications of intangible resources of an organization with a particular focus on the evolution of these typologies is done. The relationship between intangible resources, intellectual capital of the organization and intangible assets of the company were indicated.